The readiness of higher education institutions in the Sultanate of Oman for the fourth industrial revolution and Oman’s vision 2040 from the point of view of the academic staff and experts - Al-Saiari, Mashael Awadh; Al-Ani, Wajeha Thabit; Al-Abri, Khalaf Murhoon (Journal of Educational and Psychological Sciences, 2022)
The study aimed to reveal the readiness of higher education institutions for the fourth industrial revolution and Oman future vision 2040. It also investigated the impact of experience and the gender of the academic staff on their perceptions of readiness. The study used a mixed approach in which a questionnaire and interviews were conducted to collect data. The study sample of the questionnaire consisted of (475) academic staff while the interviews consisted of (16) leaders of higher education and experts in the fourth industrial revolution. According to the results, the questionnaire obtained a total average (3.20 out of 5) with medium readiness generally. At the level of the seven dimensions; the learning and skills got the highest average (3.37), then infrastructure and digital transformation with an average of (3.28), followed by future foresight with an average of 3.26, then planning and policies with an average of (3.18). Then, community partnership got an average of (3.17), followed by scientific research which got an average of (3.14), and finally international cooperation obtained an average of (2.99). Simmilary, the results of the qualitative interviews about the readiness of higher education institutions for the Fourth Industrial Revolution and the achievement of Oman’s 2040 vision showed a medium average level of readniess. The study also revealed that there are differences in favor of the variables regarding to years of experience in the dimension of digital transformation and infrastructure related to those with more than (15) years of experience. Also, it revealed that there are differences according to gender in all dimensions for males. Based on the results, the researcher made a number of recommendations such as focusing on providing students with the required skills in the era of the Fourth Industrial Revolution, improving the educational environment, and employing the new technologies, and developing a strategy to keep pace with the Fourth Industrial Revolution in higher education. The study ended with a proposal suggested studies on the subject.
Keywords: Fourth Industrial Revolution; Requirements; Readiness; Higher Education Institutions; Oman 2040 Vision